Pengaruh Pijat Bayi Terhadap Bounding Attachment di Ruang Dahlia RSD dr. Soebandi Jember - Sri Wahyuni; Dini Kurniawati; Hanny Rasni (Pustaka Kesehatan, 2018)
Bounding attachment is very important for newborn to be adapted to the new environment. Mother’stouch can help babies adapt to environmental differences between inside the womb and outside thewomb. How to improve the bounding attachment is early breastfeeding initiation, rooming in,kangaroo mother care for premature, and baby massage. The purpose of this research is todetermine the impact of baby massage to bounding attachment. The method of research was quasiexperimental with design of research pretest-post test with control group. This research is in Dahliaroom in dr. Soebandi general Hospital, with samples as 40 respondent with 20 people forexperimental group and 20 people for control group. The research use standard operationalprocedure of baby massage and quality of bounding attachment questionnaire. Take the sample bypurposive sampling. The results of research is give difference in average pretest-post test on theexperimental group of -7,35 whereas on the control group of -2,55. Statistic test result obtained the pvalue 0.001, this mean on the alpha 5% can be expressed there is influence of baby massage forbounding attachment. There are several factors that influence to the bounding attachment that isemotional health of parent, family support, the proximity and match of the parents and baby. Theresult of this research are recommended as the nursing treatment and to the public especiallymother postpartum.Keywords : baby massage, bounding attachment